(untitled) (Studia theodisca, 2014)
Revising Heidegger’s dictum about Hölderlin being «the poet’s poet» and the philosopher’s remarks on the «essence» of poetry, the emphasis is shifted on the “method” of poetry, a crucial question for Hölderlin, which is here analyzed on the basis of his “Homburg poetology” (cfr. the table in the appendix) as well as of his poetry and prose.